Enculturation and Attitudes Toward Intimate Partner Violence and Gender Roles in an Asian Indian Population: Implications for Community‐Based Prevention. Issue 3 (11th February 2014) - Yoshihama, Mieko; Blazevski, Juliane; Bybee, Deborah
Abstract: This study examined the relationships among enculturation, attitudes supporting intimate partner violence (IPV‐supporting attitudes), and gender role attitudes among one of the largest Asian Indian population groups in the US. Data were collected via computer‐assisted telephone interviews with a random sample of Gujarati men and women aged 18–64 in Metropolitan Detroit. Using structural equation modeling, we modeled the effects of three components of enculturation (behavior, values, and community participation) on gender role attitudes and IPV‐supporting attitudes among married respondents ( N = 373). Analyses also accounted for the effects of respondent age, education, religious service attendance, perceived financial difficulty, and lengths of residence in the US. The second‐order, overall construct of enculturation was the strongest predictor of IPV‐supporting attitudes (standardized B = 0.61), but not gender role attitudes. Patriarchal gender role attitudes were positively associated with IPV‐supporting attitudes (B = 0.49). In addition to the overall effect of the enculturation construct, two of the components of enculturation had specific effects. "Enculturation‐values" had a specific positive indirect association with IPV‐supporting attitudes, through its relationship with patriarchal gender role attitudes. However, "enculturation‐community participation" was negatively associated with IPV‐supporting attitudes, suggesting the importance of community‐based prevention of IPV among this immigrant population group.